2020
DOI: 10.3390/cells9061426
|View full text |Cite
|
Sign up to set email alerts
|

HIV Nef and Antiretroviral Therapy Have an Inhibitory Effect on Autophagy in Human Astrocytes that May Contribute to HIV-Associated Neurocognitive Disorders

Abstract: A significant number of people living with HIV (PLWH) develop HIV-associated neurocognitive disorders (HAND) despite highly effective antiretroviral therapy (ART). Dysregulated macroautophagy (autophagy) is implicated in HAND pathogenesis. The viral protein Nef, expressed even with suppressive ART, and certain antiretrovirals affect autophagy in non-CNS cells. Astrocytes, vital for CNS microenvironment homeostasis and neuronal health, require autophagy for their own homeostasis. We hypothesized that extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 103 publications
(162 reference statements)
0
17
0
Order By: Relevance
“…In particular, the HIV proteins TAT, NEF, and ENV are involved in this regulation by either blocking or stimulating autophagy through direct interaction with autophagy proteins and/or modulation of the mTOR pathway [ 59 , 60 , 61 , 62 ]. Likewise, ART drugs [ 63 , 64 , 65 ] and aging [ 66 , 67 ] have been associated with dysregulation of autophagy. These different factors associated with dysregulation of autophagy may contribute to autophagosome and multivesicular bodies fusion [ 68 ] and induce larger EV release.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the HIV proteins TAT, NEF, and ENV are involved in this regulation by either blocking or stimulating autophagy through direct interaction with autophagy proteins and/or modulation of the mTOR pathway [ 59 , 60 , 61 , 62 ]. Likewise, ART drugs [ 63 , 64 , 65 ] and aging [ 66 , 67 ] have been associated with dysregulation of autophagy. These different factors associated with dysregulation of autophagy may contribute to autophagosome and multivesicular bodies fusion [ 68 ] and induce larger EV release.…”
Section: Discussionmentioning
confidence: 99%
“…Cells respond to mitochondrial or ER stress by inducing autophagy. However, as highlighted in these reviewed studies, autophagy upregulation can also lead to autophagy exhaustion [ 7 ], may be toxic by itself [ 17 , 18 , 27 ], or autophagy may fail to be upregulated or is inhibited [ 11 , 12 , 13 , 14 , 15 , 20 , 25 , 26 , 27 ], subsequently leading to decreased cell viability and death ( Table 1 ). Thus, these studies reinforce the major significance of autophagy dysregulation as a mechanism underlying drug toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Three comprehensive studies showed that three-drug regimens containing two NRTI plus an ISTI inhibit autophagy, and may contribute to HAND in PLWH [ 25 , 26 , 27 ]. A two-part study addressed the effects of tenofovir disoproxil fumarate (TDF), emtricitabine (FTC), and dolutegravir (DTG) on autophagy and inflammatory genes/proteins in primary rat microglia.…”
Section: Combination Antiretroviral Drugsmentioning
confidence: 99%
See 2 more Smart Citations